Essential Oil and Smoke Components of Artemisia absinthium and Hagenia abyssinica - Nigussie Kebie; Melaku Assefa Sisay (International Journal of Food Science)
Hagenia abyssinica and Artemisia absinthium are widely distributed tree species in Ethiopia and known for their traditional medicinal uses. The present study was conducted to determine the essential oil and smoke constituents of H. abyssinica and A. absinthium leaves using GC-MS. The main components of the A. absinthium essential oil were valencene (5.48%), bornyl acetate (5.15%), and trans-cinnamic acid (4.34%). 2-Bornanone (18.54%), o-cymene (12.80%), and nerolidol (7.04%) were the dominant components of the MeOH fraction of the smoke derived from the leaves of A. absinthium, while 2-propenoic acid butyl ester (46.49%), heptadecane (10.66%), and 9-octylheptadecane (7.78%) were the major components of the n-hexane fraction. The main components of the H. abyssinica essential oil were cis-davanone (14.73%), Aristolediene (9.31%), and cryptone (6.50%). β-Myrcene (12.59%), neophytadiene (11.54%), and limonene (11.27%) were the dominant components of the MeOH fraction of the smoke derived from the leaves of H. abyssinica. 1,3,5,7-Cyclooctatetraene (33.58%), prehnitene (7.01%), and heptadecane (5.46%) were the dominant components of the n-hexane fraction of the smoke derived from the leaves of H. abyssinica. The smoke components of A. absinthium and H. abyssinica were reported here for the first time.